1984
DOI: 10.1289/ehp.8455129
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide injury to the lung.

Abstract: Radionuclide injury to the lung has been studied in rats, hamsters, dogs, mice and baboons. Exposure of the lung to high dose levels of radionuclides produces a spectrum of progressively more severe functional and morphological changes, ranging from radiation pneumonitis and fibrosis to lung tumors. These changes are somewhat similar for different species. Their severity can be related to the absorbed radiation dose (measured in rads) produced by alpha, beta or gamma radiation emanating from various deposited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Whether these initial pathological changes lead to any long-term lesions should be investigated in the future. Previous studies investigating the effects of inhaled radioactive plutonium, an α-emitter, showed that rats died with severe pulmonary edema at higher radiation doses, while radiation pneumonitis and emphysema developed at lower doses (Lundgren et al 1981 ; Dagle and Sanders 1984 ; Scott et al 1990 ). In the present study, occasional inflammations were observed in the lung in control group.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these initial pathological changes lead to any long-term lesions should be investigated in the future. Previous studies investigating the effects of inhaled radioactive plutonium, an α-emitter, showed that rats died with severe pulmonary edema at higher radiation doses, while radiation pneumonitis and emphysema developed at lower doses (Lundgren et al 1981 ; Dagle and Sanders 1984 ; Scott et al 1990 ). In the present study, occasional inflammations were observed in the lung in control group.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, researchers have tried for decades to dissect the mechanisms that underlie the initiation and progression of these events in the hope of identifying potential targets for prevention and mitigation, with the majority of this work making use of rodent (mainly murine) models that have been subjected to localized high dose, single exposures followed by tissue analysis of the subsequent molecular, biochemical, and pathologic changes (Rubin et al 1992, Hong et al 2003, Dagle & Sanders 1984, Calveley et al 2010). A consistent finding in such studies has been a chronically dysregulated lung environment, characterized by cyclical “waves” of cytokine expression in the irradiated tissue, principally proinflammatory in nature; these “waves” have been shown to appear at the time of injury, persist through the initiation of pneumonitis and continuing until the appearance of tissue remodeling and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Once inhaled into the lungs, much of the radiation energy will get absorbed by cells, tissues, and organs. The association of radioactive exposure and lung cancer has been well documented in populations exposed to residential radon 14,15 , children in nuclear-contaminated areas 16 , Mayak workers 17,18 , fluorspar miners 19 , and workers in Uranium mines 20,21 , mills 22,23 , or enrichment 24 . The correlation between lung carcinoma and internally deposited radionuclides were reviewed by Bair 25 , Harrison and Stather 26 , Harrison and Muirhrad 27 , and Raabe 28 .…”
Section: Introductionmentioning
confidence: 99%